Criminality rates in those sentenced for femicide in Mexico - Díaz-Sánchez, Azucena; Gurrola-Peña, Gloria Margarita; Moysen-Chimal, Alejandra; Esparza del Villar, Oscar Armando; Villaveces-López, Martha (Universidad y Salud, 2023)
Introduction: Violence against women is a problem that affects the worldwide population, with its maximum expression being femicide. Due to the recent and unequal legislation regarding this phenomenon, recent studies have focused on identifying types of aggressors where criminal behavior plays an important role as a risk factor. Likewise, very few studies exist with people who have committed femicide. Objective: To determine the criminality rates in those sentenced for the crime of femicide. Materials and methods: A list with 20 dimensions was used to evaluate 62 people arrested for the crime of femicide. Results: 4 levels of criminality were found, which can be classified from low to high; the principal indicators that marked differences between these levels where domestic violence and a history of alcohol and drug use. Conclusion: The indicators that marked the differences between the levels of criminality are a history of intimate partner violence used to resolve conflicts which is associated with use of alcohol and psychoactive drugs.